Efficacy and safety of Saireito (TJ-114) in patients with atrial fibrillation undergoing catheter ablation procedures: A randomized pilot study. - Tetsuma Kawaji; Satoshi Shizuta; Hidenori Yaku; Kazuhisa Kaneda; Fumiya Yoneda; Shushi Nishiwaki; Munekazu Tanaka; Takanori Aizawa; Shun Hojo; Kenji Nakatsuma; Masashi Kato; Takafumi Yokomatsu; et al. (PLoS ONE)
Background Early arrhythmia recurrences commonly occur after atrial fibrillation (AF) ablation because of irritability and inflammation of left atrium. We hypothesized that short-term use of Saireito would be effective in reducing frequent atrial tachyarrhythmias in the early-phase post-ablation. Methods One hundred patients undergoing catheter ablation for symptomatic AF were randomly assigned to either a 30-day use of Saireito or control group. The primary endpoint was total number of episodes of frequent atrial tachyarrhythmias including definite recurrent AF and frequent premature atrial contractions during the 30-day treatment period post-ablation. Results Three (6.0%) out of 50 patients treated with Saireito discontinued the drug because of adverse symptoms. The Saireito group was associated with a numerically lower number of episodes of frequent atrial tachyarrhythmias than the control group (3.1 versus 5.2 times, P = 0.17). The mean daily episodes of frequent atrial tachyarrhythmias were significantly fewer in the Saireito group during Day-6 to Day-10 (0.12/day versus 0.27/day, P = 0.03), and during Day-11 to Day-15 (0.08/day versus 0.24/day, P = 0.001). The prevalence of adverse symptoms during the 30-day treatment period was significantly higher in the Saireito group (18.0% versus 2.0%, P = 0.005). Conclusions Thirty-day use of Saireito following AF ablation was associated with a tendency toward reduced number of episodes of frequent atrial tachyarrhythmias during the treatment period, with more pronounced effect in the first two weeks.